Raising the Neanderthal (molecules) from the dead: a proposal for in vivo resurrection of Neanderthal haemoglobin for the investigation of biochemical adaptations for cold tolerance - Katherine McLean (Research Ideas and Outcomes, 2024)
Since the first discoveries of Neanderthal fossils, their derived characteristics, such as increased robusticity, have engaged researchers. Adaptation to cold environments has been hypothesised to explain such traits and this hypothesis has driven the majority of discourse. This proposal seeks to examine this hypothesis and locate evidence of Neanderthals being physiologically adapted to cold at the biomolecular level. Haemoglobin is a biomolecule that has been previously demonstrated to adapt to cold in some species, driven by the inhibition of the protein’s function by low temperatures. Neanderthal haemoglobin is extinct; however, using pre-sequenced genomic data, I propose to resurrect Neanderthal haemoglobin so I can examine the consequences of lowered temperature on its function. This project could potentially detect signs of cold adaptation in the Neanderthal globin genes and provide empirical evidence for the cold adaptation hypothesis.